Adenomatoid Tumor: A Review of Pathology With Focus on Unusual Presentations and Sites, Histogenesis, Differential Diagnosis, and Molecular and Clinical Aspects With a Historic Overview of Its Description. (November 2020) - Karpathiou, Georgia; Hiroshima, Kenzo; Peoc'h, Michel
Abstract : Adenomatoid tumors have been described almost a century ago, and their nature has been the subject of debate for decades. They are tumors of mesothelial origin usually involving the uterus, the Fallopian tubes, and the paratesticular region. Adenomatoid tumors of the adrenal gland, the liver, the extragenital peritoneum, the pleura, and the mediastinum have been rarely reported. They are usually small incidental findings, but large, multicystic and papillary tumors, as well as multiple tumors have been described. Their pathogenesis is related to immunosuppression and to TRAF7 mutations. Despite being benign tumors, there are several macroscopic or clinical aspects that could raise diagnostic difficulties. The aim of this review was to describe the microscopic and macroscopic aspects of adenomatoid tumor with a special focus on its differential diagnosis and pathogenesis and the possible link of adenomatoid tumor with other mesothelial lesions, such as the well-differentiated papillary mesothelioma and the benign multicystic mesothelioma, also known as multilocular peritoneal cysts.